PENGGUNAAN APLIKASI MOBILE BANKING DALAM MENINGKATKAN KEPUASAN NASABAH BANK BSI MEDAN PULO BRAYAN - Rendi Setiawan Purba; Khairina Tambunan (JOURNAL SAINS STUDENT RESEARCH, 2024)
The increasing popularity of mobile banking creates great opportunities for the banking industry to expand their business, but also brings challenges to satisfy and retain customers. The purpose of this research is to see how the use of mobile banking applications increases customer satisfaction at BSI Medan Pulo Brayan. For this study, a quantitative research methodology was followed and primary and secondary data were collected. For primary data collection, a questionnaire was designed, tested first and then administered. All items regarding the measurement of variables were completely adopted from previous research and carefully rearranged so that all items can be applied to the adoption of BSI Pulo Brayan Medan mobile banking. According to the output in the "Coefficients" section, it is known that the sig values of the two variables, namely Security (X1) = 0.005 and Cost (X2) = 0.000 <0.05. This indicates that the security variable (X1) and cost (X2) have a significant effect on the satisfaction variable (Y)..